2017
DOI: 10.1002/2016ja023274
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear effects associated with quasi‐electrostatic whistler waves relevant to that in radiation belts

Abstract: A model is proposed to study the dynamics of high‐amplitude quasi‐electrostatic whistler waves propagating near resonance cone angle and their interaction with low‐frequency kinetic Alfvén waves (KAWs) in Earth's radiation belts. The wave dynamics clearly indicates the whistlers having quasi‐electrostatic character when propagating close to resonance cone angle. A high‐amplitude whistler wave packet is obtained using the present analysis which has also been observed by S/WAVES (STEREO/WAVES) instrument onboard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The quasi‐field aligned wave normal angle assumption is consistent with the observation in Figure 2c. Oblique chorus waves have been observed in the previous studies (e.g., Li et al., 2016), and their precipitation effects (Goyal et al., 2017, 2018) and the subsequent MIA energy interplay will be an interesting future study.…”
Section: Stet Code Settingmentioning
confidence: 72%
“…The quasi‐field aligned wave normal angle assumption is consistent with the observation in Figure 2c. Oblique chorus waves have been observed in the previous studies (e.g., Li et al., 2016), and their precipitation effects (Goyal et al., 2017, 2018) and the subsequent MIA energy interplay will be an interesting future study.…”
Section: Stet Code Settingmentioning
confidence: 72%
“…Previous studies have also shown abundant large amplitude oblique whistler-mode waves with wave normal angles close to the resonance cone angle (e.g., Cattell et al, 2008;Li et al, 2016). The nonlinear effects for these quasi-electrostatic whistler-mode waves can be very different from parallel waves (Artemyev et al, 2013;Goyal et al, 2017;Goyal et al, 2018;Zhang et al, 2022a) and further investigation is needed to fully understand their roles in electron precipitation.…”
Section: Discussionmentioning
confidence: 98%
“…Chorus subpackets consist of wave packets characterized by modulated amplitudes, typically within a timescale of ∼10–100 milliseconds in the Earth's magnetosphere (Goyal et al., 2017; Mourenas et al., 2022; Santolík et al., 2003; Tsurutani et al., 2009; Zhang et al., 2020). They are also observed in the magnetospheres of other planets (Menietti et al., 2012; Reinleitner et al., 1984), as well as in laboratory plasma (Van Compernolle et al., 2016).…”
Section: Introductionmentioning
confidence: 99%